Pengaruh Red Flag, Pelatihan, Independensi, dan Beban Kerja terhadap Kemampuan Auditor Mendeteksi Fraud dengan Skeptisisme Profesional sebagai Variabel Intervening - Gizta, Aulia Dewi; Anugerah, Rita; Andreas, Andreas (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The purpose of this study was to examine the effect of red flag, training, independency, and workload on the auditor’s ability to detect fraud by professional skepticism as intervening variable. The population of this study is auditor who work on Financial and Development Supervision Agency of Riau Province. The samples are determined based on sensus method, so that all the population used as a sample. Total respondents used in this research are 58 auditors. Data collection methods are carried out with survey method through questionnaire. The results of this study find that the red flag, training, and independence have significantly effect toward professional skepticism; didn’t find direct effect of workload toward professional skepticism; redflag, training, and professional skepticism have direct effect toward fraud detection ability of auditors; didn’t find direct effect of independency and workload toward fraud detection ability of auditors; redflag and training have indirect effect toward fraud detection ability of auditors through professional skepticism; didn’t find indirect effect of independency and workload toward fraud detection ability of auditors through professional skepticism.